A method for agglomerating and purifying phosphate rock by compression molding

Through the compression molding process and the introduction of roasting additives, the existing phosphate ore blocking purification process is solved, and the efficient and economical phosphate ore purification effect is achieved, and the fluorapatite in phosphate concentrate is used to maximize the use.

CN119263230BActive Publication Date: 2025-03-25XIAN RES & DESIGN INST OF WALL & ROOF MATERIALS CO LTD +2

Patent Information

Application Number
CN202411783633.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing phosphate ore block purification process is low efficiency and poor practicality, especially the small particle size and high carbonate content of phosphorus concentrate, which leads to a mild roasting environment, low combustion efficiency, and high investment cost.

Method used

The compression molding process is adopted to accurately control the amount of water added in the material and introduce the auxiliary material compression molding agent to ensure that the material has sufficient plasticity, and targeted calcination additives are introduced to reduce the sintering vitrification temperature and form dense and hardened bulk phosphorus concentrate.

Benefits of technology

It effectively improves the efficiency and practicality of phosphate ore purification, reduces sintering vitrification temperature, reduces energy consumption and equipment costs, and maximizes the release, purification and utilization of fluorapatite in phosphate concentrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for purifying phosphate ore by compression molding, which uses phosphate concentrate as a main material, compression molding agent and roasting aid as auxiliary materials, and sequentially mixes materials, stands, breaks up, ages, compression molding, dries, and roasts to prepare block-shaped purified phosphate concentrate. The invention adopts a compression molding process, and by accurately controlling the amount of water added to the material, combined with the introduction of an auxiliary material compression molding agent, ensures that the material has sufficient plasticity and is smoothly pressed and molded, and at the same time, introduces a roasting aid in a targeted manner to obtain a dense block phosphate concentrate with a certain hardness, effectively reduces the sintering vitrification temperature, and maximizes the release, purification and utilization of fluoroapatite in the phosphate concentrate, providing a theoretical basis for large-scale production, and is suitable for the field of ore utilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ore purification, and in particular relates to a method for purifying phosphate ore by agglomeration by a compression molding method. Background Art

[0002] Phosphate rock is an important chemical mineral raw material with a wide range of applications. It can be used to produce pure phosphorus (yellow phosphorus, red phosphorus) and chemical raw materials, and can also be used to make animal feed.

[0003] my country's phosphate resources are mainly medium and low-grade phosphate ores, with few rich ore resources. In addition, the rich ore resources have been gradually consumed in recent years and their prices have been rising. Domestic phosphorus chemical companies have to use phosphate concentrates after beneficiation of medium and low-grade phosphate ores for production. At present, the main process for processing phosphate ore to produce yellow phosphorus is the electric furnace method. In order to meet production requirements, the phosphate ore entering the furnace must have uniform particle size, low pulverization rate, low water content, low carbonate content, and a certain thermal strength. However, due to the small particle size of the phosphate concentrate, it must be agglomerated before entering the furnace.

[0004] The more mature agglomeration methods currently available include sintering, pelletizing, briquetting, and nodulation. For phosphate ores with low phosphorus content and high carbonate content, the carbonate content can be effectively reduced after roasting. Therefore, the research on the sintering and purification process of phosphate ore is of great significance. Although there have been reports on the sintering of phosphate ores in China, the focus has been on exploring the feasibility of sintering, and there is still a lack of systematic research from the basic properties of raw materials to the sintering process. At present, the commonly used sintering and purification process for phosphate ore is the pellet roasting method, which is mostly carried out using a belt or ring sintering machine. The sintering and purification process was first used in the purification of iron ore, and was later transplanted into the phosphate ore purification industry. However, the inventor's project team found in practice that the sintering purification process has low efficiency and poor practicality for phosphate ore purification. The reasons are as follows: (1) Compared with iron ore, the alkaline metal content in phosphate ore is not high, and the fluxing substances mainly come from calcium feldspar and sodium feldspar. This sintering system has relatively mild requirements for the combustion environment. A "hard" combustion environment, that is, a combustion environment temperature that is lower than the fire source temperature, is likely to form a glass shell on the outer part of the pellet, preventing carbonate decomposition and making it difficult to remove carbon dioxide; (2) Excessively high flame temperature has no promoting effect on phosphate ore purification, so the combustion efficiency is low; (3) The investment cost is high and the effect is relatively simple. In addition, the commonly used method of phosphate ore agglomeration is roller pressing into balls, which is to fully mix phosphate ore powder, binder and water, and then send them into a high-pressure roller press to press them into pellets, and then dry them to obtain finished balls. This agglomeration method has the disadvantages of small ball size, low green body strength, and the need for external binders (clay). In particular, the amount of external binders is as high as 20%, which seriously affects the sintering system, making it difficult to control the roasting temperature and insulation time, which in turn seriously affects the quality of the finished product. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for phosphate rock agglomeration and purification by compression molding in view of the deficiencies of the above-mentioned prior art. The method adopts a compression molding process to accurately control the amount of water added to the material, combined with the introduction of an auxiliary material compression molding agent, to ensure that the material has sufficient plasticity and is smoothly pressed and molded, and at the same time, a roasting aid is introduced in a targeted manner to obtain a dense block of phosphate concentrate with a certain hardness, effectively reduce the sintering vitrification temperature, and solve the problem of low purification efficiency and poor practicality of the existing phosphate rock agglomeration and purification process.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for purifying phosphate ore by compression molding, characterized in that the method uses phosphate concentrate as the main material, and compression molding agent and roasting aid as auxiliary materials, and sequentially mixes the materials, stands, breaks up, ages, compression molds, dries, and roasts to prepare block-shaped purified phosphate concentrate.

[0007] The present invention tests and studies the performance of phosphate concentrate and finds that the phosphate concentrate is relatively "sticky" (sticky to the hand) as a whole, has "pseudoplasticity" (feeling good but poor plasticity index), and its plasticity index (representing the range of plastic water content) is only 6-7, while the better material is about 10, indicating that the plasticity of the phosphate concentrate is poor. At the same time, the components in the phosphate concentrate are mainly apatite, dolomite, spinel and quartz, and there are also some amorphous phases, and the P element is mainly enriched in the form of apatite, including fluoroapatite, chlorapatite, and hydroxyapatite, and the most common one is fluoroapatite.

[0008] Based on the above research results, the present invention extends the tunnel kiln brick making process to the phosphate rock purification process to maximize the advantages of the tunnel kiln, such as large output, superior roasting environment, and mature process route, but it also faces many process difficulties.

[0009] First, due to the poor molding performance of phosphate concentrate, when the traditional brick extrusion molding process is used, the green body has many burrs and is easy to break, and continuous production cannot be achieved. When the ceramic pressing molding process suitable for materials with low moisture content (3%~5%) is used, the molding pressure is large, the equipment investment is large, and the production efficiency is insufficient. In response to this problem, the present invention proposes a compression molding process for the first time, which uses the remaining plasticity in phosphate concentrate for molding. However, this molding process has precise requirements on the amount of water added to the material. If there is too much water, the green body will seep water and stick to the mold, and if there is too little water, it will be difficult to plastically mold. Therefore, the present invention introduces an auxiliary material compression molding agent, which uses the compression molding agent to lubricate the material particles and retain water, thereby ensuring the smooth implementation of the compression molding process. It has been tested that the bulk density of the pressed body obtained after compression molding of the present invention can reach 2.1g / cm³~2.3g / cm³, which is much higher than the roller ball technology (1.8g / cm³). The pressed body can meet the problem of the stacking height of the body during the tunnel kiln sintering process, thereby improving the output and preparation efficiency; at the same time, the study found that when the strength of the pressed body is 2.10MPa~2.20MPa, the compression molding process is the most economical and reasonable. When the strength of the pressed body is above 3MPa, it can meet the problem of the stacking height of the body during the tunnel kiln sintering process, and avoid crushing and cracking during the stacking process.

[0010] Secondly, in order to meet the requirements of phosphate ore purification, the pressed green body must be sintered into the kiln to basically reach the level of sintering vitrification (water absorption rate less than 5% is generally the judgment standard for vitrification into porcelain). Only when this level is reached, the thermal strength, powder passing rate and purification efficiency of the pressed green body can meet the production requirements. In response to this demand, the present invention conducts in-depth research on the sintering mechanism of phosphate concentrate and finds that tricalcium phosphate in most phosphate ores exists in the form of fluoroapatite, which does not participate in the actual reaction during the sintering process. In addition, clay and feldspar play a role in fluxing, that is, the sintering system is a "tricalcium phosphate-clay-feldspar" system. Specifically, unlike other conventional sintering systems, such as ceramic sintering systems that use clay feldspar as the main raw material, part of the active silicon and aluminum in the clay itself forms mullite crystals to form a skeleton through high temperature, and the other part of the active silicon and aluminum gather cations to form feldspar, and then combine the feldspar in the raw material to melt into a liquid phase at high temperature to fill the gaps in the mullite crystal skeleton. In the sintering process of the present invention, carbonates represented by dolomite decompose, and carbon dioxide is released, leaving active calcium and magnesium, which are combined with active silicon and aluminum in the clay to produce feldspar fluxing materials, among which calcium feldspar plays a key role. After calcium feldspar melts, it forms a liquid phase, fills the gaps between fluoroapatite crystals, forms a dense whole, completes the sintering and vitrification process, and forms a dense block with a certain hardness after cooling. Therefore, the "tricalcium phosphate-clay-feldspar" system of the present invention is more sensitive to the temperature of the sintering and vitrification process, and the sintering and vitrification process can be completed without keeping warm for too long after reaching the appropriate roasting temperature. Usually, the temperature of the sintering and vitrification process is 1150℃~1200℃, which is too high for tunnel kilns, and the refractory grade needs to be improved, which increases the preparation cost. Therefore, the present invention adds auxiliary material roasting aids, introduces different cations, combines active silicon and aluminum to form different types of feldspar, changes the type of fluxing material, and improves the formation efficiency and type of fluxing material, such as introducing sodium ions to form albite, introducing quicklime to form calcium feldspar, and introducing quartz to provide an acidic environment. The fluxing efficiency of albite and calcium feldspar is higher in the acidic molten state, and kaolinite is introduced to provide active silicon and aluminum, which is helpful for the formation of feldspar-like substances, thereby reducing the sintering and vitrification temperature of the pressed body to 1100℃~1150℃, which meets the use requirements of tunnel kilns.

[0011] Again, for the characteristics of some amorphous phases of phosphate concentrate containing some fluoroapatite, the present invention has found that crystals are more likely to precipitate in a weakly acidic and viscous melt environment. Therefore, the present invention uses a roasting aid and controls the composition of the roasting aid so that the roasting aid decomposes active aluminum and silicon at 600°C~900°C. Aluminum can improve the pH of the melt, and alkali can improve the viscosity of the melt. In particular, kaolin has excellent ability to decompose active aluminum and silicon, and the purity of the silicon and aluminum contained is also high, so that the melt environment formed by the "tricalcium phosphate-clay-feldspar" system of the present invention is weakly acidic and has a large viscosity, which improves the physical and chemical environment of the melt, creates an environment more suitable for crystal growth, promotes crystal precipitation, accelerates crystal formation and growth, and effectively "precipitates" the fluoroapatite substance in the amorphous phase to form new crystals. In addition, during the research process of the present invention, it was found that part of the fluoroapatite in the phosphate concentrate was "confined" in the amorphous phase. The main reason is that the magma cooling rate is fast during the diagenesis process, and some crystals have no time to grow. In this regard, the present invention controls the cooling system after roasting to reactivate this part of the material, so that the crystals are re-precipitated and exist stably, which is beneficial to further improve the effective phosphorus content in the bulk apatite after purification, maximizes the release, purification and utilization of fluoroapatite in phosphate concentrate, and increases economic value.

[0012] According to tests, when the density of purified phosphate concentrate, i.e. purified phosphate rock, is 2.0g / cm³~2.1g / cm³, it indicates that its sintering and vitrification degree is good. When the phosphorus content of purified phosphate concentrate is above 35%, the comprehensive economic efficiency is the highest. Moreover, the powder rate of purified phosphate rock after crushing does not exceed 5%, which meets the requirements of the subsequent conventional pyrophosphate production process.

[0013] The above-mentioned method for agglomeration and purification of phosphate ore by compression molding is characterized in that the mass content of phosphorus in the phosphate concentrate is 15%~25% in terms of P2O5, and the particle grading of the phosphate concentrate is: 10%~15% of 1mm~2mm coarse aggregate, 85%~90% of 0~1mm fine aggregate, wherein the mass ratio of fine aggregate less than 200 mesh in the fine aggregate is not less than 30%; the compression molding agent is a mixture of methyl cellulose, montmorillonite, and sodium hexametaphosphate in a mass ratio of 28:70:2, and the blending amount of the compression molding agent is 3%~5% of the mass of the phosphate concentrate; the roasting aid is a mixture of sodium carbonate, quartz, kaolinite and quicklime in a mass ratio of 0.5:15:74:10.5, and the blending amount of the roasting aid is 2%~8% of the mass of the phosphate concentrate; the particle size of the auxiliary material compression molding agent and the roasting aid are both less than 150 mesh.

[0014] The above-mentioned method for agglomeration and purification of phosphate rock by compression molding is characterized in that the method comprises the following steps:

[0015] Step 1, weighing phosphate concentrate including coarse aggregate, fine aggregate, compression molding agent, roasting aid, and water as required;

[0016] Step 2: Mix the fine aggregate weighed in step 1 with the compression molding agent, the baking aid, and the water, and then seal and let stand for 2 hours to 4 hours to obtain a first mixture;

[0017] Step 3, breaking up the first mixed material obtained in step 2, and passing it through a 10-mesh sieve until there is no residue on the sieve, to obtain a sieved first mixed material;

[0018] Step 4: Evenly mix the sieved first mixture obtained in step 3 and the coarse aggregate weighed in step 1 and seal the mixture to obtain a second mixture;

[0019] Step 5: sealing and aging the second mixed material obtained in step 4 at 15° C. to 25° C. for 8 h to 12 h to obtain an aged material;

[0020] Step 6: Compression-molding the aged material obtained in step 5 at a pressure of 20 MPa to 25 MPa to obtain a pressed body;

[0021] Step 7: Place the pressed green body obtained in step 6 in an oven and dry at 105° C. for 12 h to 18 h;

[0022] Step 8: Place the pressed green body dried in step 7 in an electric furnace for roasting to obtain purified phosphate ore.

[0023] The above-mentioned method for agglomeration and purification of phosphate rock by compression molding is characterized in that the compression molding in step 6 is a method of using pressure to press the material placed in the mold to a tight structure to form a green body with a certain shape and strength, wherein the moisture content of the material placed in the mold is the compression molding moisture, which has the following meanings:

[0024] Compression molding moisture = plastic limit Wp-2%

[0025] =(Gp / Gs)×100%-2%

[0026] Gp is ​​the mass of water contained when the plastic state changes into a semi-solid state; Gs is the mass of absolutely dry clay, which can be directly measured by the strip rubbing method, or obtained by the combined measurement method of liquid and plastic limits; when the moisture content of compression molding is less than 5%, it is considered that the material is not suitable for the method of the present invention.

[0027] The existing large-scale production compression molding process, such as the compression molding process of ceramic bricks and refractory bricks, usually adopts large equipment such as 2000-ton molding machines, and the material is compacted by an absolutely large enough pressure to ensure the high density of the green body after molding, but the equipment investment is large, and the number of blocks formed at a time is 1 to 5, and the molding moisture is basically 3% to 5%, and the equipment output or production capacity is insufficient. The present invention intends to use the more widely used 1200-ton molding machine for compression molding, and the number of blocks formed at a time is 40, which not only reduces the equipment cost but also improves the compression efficiency. Since the pressure of the equipment used is obviously insufficient, the present invention controls the moisture content of the compression molding so that the moisture content of the material approaches the plastic limit index, ensures that the material has sufficient plasticity, usually in a state between powder and mud, ensures the molding of the pressed green body, avoids the moisture content of the material being too low and the plasticity being insufficient, resulting in insufficient compactness of the pressed green body, and the moisture content of the material being too high to form mud and form a sticky film.

[0028] The above-mentioned method for agglomeration and purification of phosphate rock by compression molding is characterized in that the roasting temperature determination process described in step eight is: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and sealed for aging for 1 hour, 30g of round cake samples with a diameter of φ50mm are taken, and the round cake samples are tested for firing after drying. The test firing temperatures are 1100°C, 1125°C, 1150°C, 1175°C and 1200°C respectively, the heating rate is 4°C / min, the insulation time is 30min, and then different test The product obtained at the calcination temperature is tested for water absorption by the boiling method. When the water absorption of the product is 5% to 8%, the corresponding calcination temperature is considered to be the optimal calcination temperature, i.e., the calcination temperature. When the calcination temperature is higher than 1175°C, 2% of the calcination aid is added to the raw material phosphate concentrate in batches, and the above-mentioned water-added sealing aging, sample pressing, drying and trial calcination, and water absorption rate detection processes are repeated to reduce the calcination temperature. When the amount of the calcination aid added is greater than 8%, the calcination temperature cannot be reduced, and it is considered that the material is not suitable for the method of the present invention.

[0029] The roasting time determination process is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added, stirred evenly, and then allowed to stand for 1 hour, broken up through a 150-mesh sieve, and then sealed and aged for 2 hours, 600g~800g of the aged material is weighed and pressed into a 100mm×100mm×(30~40)mm sample, the molding pressure is 20MPa, and the sample is dried to constant weight for pre-burning. The pre-burning heating system is as follows: first, the temperature is increased from room temperature to 600°C and kept for 1 hour, then the temperature is increased to 900°C and kept for 1 hour, and then the temperature is increased to the selected optimal firing temperature for keeping warm. The keeping warm times are 1h, 2h, and 3h, respectively, and the heating rate is 4°C / min. Then, the products obtained at different keeping warm times are tested for water absorption by the boiling method. When the water absorption of the product is less than 10%, the corresponding keeping warm time is considered to be the optimal keeping warm time.

[0030] The above-mentioned method for purifying phosphate ore by compression molding is characterized in that the cooling system adopted after roasting in step eight is: cooling from the roasting temperature to 1000°C and keeping it for 1 hour, then cooling to 750°C and keeping it for 2 hours, then cooling to 400°C and keeping it for 1 hour, and then cooling to room temperature, and the cooling rate is 10°C / min.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1. The present invention makes innovations in the molding method, adopts a compression molding process, and proposes the concept of moisture in compression molding. By accurately controlling the amount of water added to the material, it is ensured that the material has sufficient plasticity and is smoothly compressed and molded, thereby avoiding the molding problem of "pseudoplastic" materials under molding pressure; further, by introducing an auxiliary material compression molding agent, the compression molding agent is used to lubricate the material particles and retain water, thereby ensuring the smooth implementation of the compression molding process.

[0033] 2. Based on the determination of the sintering system as a "tricalcium phosphate-clay-feldspar" system, the present invention introduces a targeted roasting aid to obtain a dense block of phosphate concentrate with a certain hardness, thereby effectively reducing the sintering vitrification temperature, energy consumption and equipment costs.

[0034] 3. The present invention improves the physical and chemical environment of the melt by introducing a roasting aid and controlling its composition, promotes the crystal precipitation of amorphous fluoroapatite in phosphate concentrate, and accelerates crystal formation and growth. Combined with controlling the cooling system after roasting, the amorphous fluoroapatite is further activated to precipitate and stabilize its existence, thereby maximizing the release, purification and utilization of fluoroapatite in phosphate concentrate.

[0035] 4. The present invention designs a complete briquetting and purification scheme for phosphate concentrate, provides a theoretical basis for large-scale production, and provides a new way to utilize other types of ores.

[0036] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0037] The chemical composition and mineral composition of the main material phosphate concentrate in Examples 1 to 3 of the present invention are shown in Tables 1 and 2 below, respectively.

[0038] Table 1 Chemical composition of phosphate concentrate (%)

[0039]

[0040] Table 2 Mineral composition of phosphate concentrate (%)

[0041]

[0042] Example 1

[0043] This embodiment includes the following steps:

[0044] Step 1: Determine the moisture content of compression molding

[0045] The phosphate concentrate was tested and Gp=1.1g, Gs=10.03, then the plasticity index of the phosphate concentrate, that is, the plastic limit Wp=(1.1 / 10.03)×100%=11%, and the compression molding moisture of the phosphate concentrate = plastic limit Wp-2%=11%-2%=9%; Gp is ​​the mass of water contained when the plastic state changes to a semi-solid state, and Gs is the mass of absolutely dry clay, which can be directly measured by the strip rubbing method, or obtained by the combined determination method of liquid and plastic limits;

[0046] Step 2: Determine the roasting temperature and roasting time

[0047] The roasting temperature determination process is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and sealed for 1 hour, 30g of round cake samples with a diameter of φ50mm are taken, and the round cake samples are tested after drying. The test firing temperatures are 1100℃, 1125℃, 1150℃, and 1175℃ respectively. 1200℃, heating rate 4℃ / min, holding time 30min, then the products obtained at different trial firing temperatures were tested for water absorption by boiling method, the results showed that the water absorption of the product obtained at 1200℃ was 5.5%, the water absorption of the product obtained at 1175℃ was 8.3%, and the water absorption of the products obtained below 1175℃, i.e. 1100℃, 1125℃, 1150℃ were all greater than 8%; then 2% roasting aid was added to the raw phosphate concentrate to repeat the above-mentioned water-added sealing aging, sample pressing, drying trial firing, and water absorption detection process, the results showed that the water absorption of the product obtained at 1175℃ was 5.0%, the water absorption of the product obtained at 1150℃ was 7.5%, and the water absorption of the products obtained below 1150℃, i.e. 1100℃ and 1125℃ were all greater than 8%, so the optimal firing temperature, i.e. the roasting temperature, was determined to be 1150℃, and 2% roasting aid was added at the same time;

[0048] The process of determining the roasting time is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and stirred evenly, and then it is allowed to stand for 1 hour, and then it is broken up through a 150 mesh sieve, and then sealed and aged for 2 hours. 600g~800g of the aged material is weighed and pressed into a 100mm×100mm×(30~40)mm sample, and the molding pressure is 20MPa. It is dried to constant weight for pre-burning. The pre-burning heating system is as follows: first, the temperature is increased from room temperature to 600℃ and kept for 1 hour, then the temperature is increased to 900℃ and kept for 1 hour, and then the temperature is increased to the selected optimal firing temperature, i.e., 1150℃, and kept for 1 hour, 2 hours, and 3 hours, respectively, and the heating rate is 4℃ / min. Then, the products obtained at different holding times are tested for water absorption by the boiling method. The results show that the products obtained at holding times of 2 hours and 3 hours can achieve a water absorption rate of less than 10%. Considering the energy consumption cost, the optimal holding time, i.e., the roasting time, is determined to be 2 hours.

[0049] Step 3: Phosphate rock agglomeration and purification

[0050] Step 301, weighing phosphate concentrate including coarse aggregate, fine aggregate, compression molding agent, roasting aid, and water as required; the mass content of phosphorus in the phosphate concentrate is 20.49% in terms of P2O5, and the particle size distribution of the phosphate concentrate is: 10% of 1mm~2mm coarse aggregate, 90% of 0~1mm fine aggregate, wherein the mass ratio of fine aggregate smaller than 200 mesh in the fine aggregate is not less than 30%; the compression molding agent is methyl cellulose, montmorillonite, sodium hexametaphosphate, by mass The mixture is a mixture of sodium carbonate, quartz, kaolinite and quicklime in a mass ratio of 0.5:15:74:10.5, and the amount of the calcination aid is 2% of the mass of the phosphate concentrate; the particle sizes of the auxiliary material compression molding agent and the calcination aid are both less than 150 mesh; the amount of water added is determined according to the moisture content of the phosphate concentrate in the compression molding in step 1;

[0051] Step 302, mixing the fine aggregate weighed in step 301 with the compression molding agent, the baking aid, and the water, and then sealing and standing for 2 hours to obtain a first mixture;

[0052] Step 303, breaking up the first mixed material obtained in step 302, and passing it through a 10-mesh sieve until there is no residue left on the sieve, thereby obtaining a sieved first mixed material;

[0053] Step 304, mixing the sieved first mixture obtained in step 303 and the coarse aggregate weighed in step 1 evenly and sealing them to obtain a second mixture;

[0054] Step 305, sealing and aging the second mixed material obtained in step 304 at 25° C. for 8 hours to obtain an aged material;

[0055] Step 306, compression molding the aged material obtained in step 305 under a pressure of 20 MPa to obtain a pressed body;

[0056] Step 307, placing the pressed green body obtained in step 306 in an oven and drying at 105°C for 12 hours;

[0057] Step 308, placing the pressed green body dried in step 307 in an electric furnace for roasting to obtain purified phosphate ore; the roasting system is: first heating from room temperature to 600°C and keeping warm for 1 hour, then heating to 900°C and keeping warm for 1 hour, and then heating to 1150°C and keeping warm for 2 hours, and the heating rate is 4°C / min; the cooling system adopted after the roasting is: cooling from the roasting temperature to 1000°C and keeping warm for 1 hour, then cooling to 750°C and keeping warm for 2 hours, then cooling to 400°C and keeping warm for 1 hour, and then cooling to room temperature, and the cooling rate is 10°C / min.

[0058] After testing, the indicators of the pressed green body and purified phosphate ore obtained in this embodiment all meet the production requirements. The results are shown in Table 3 below.

[0059] Table 3 Product indicators of Example 1

[0060]

[0061] The powder rate of the purified phosphate rock after crushing in Table 3 is the mass content of the material less than 3 mm after crushing.

[0062] It can be seen from Table 3 that the pressed green body prepared in this embodiment has suitable strength and density, which meets the stacking requirements of tunnel kiln sintering. The prepared purified phosphate ore has a good sintering vitrification degree and high comprehensive economic efficiency, which can meet the requirements of subsequent processes.

[0063] Example 2

[0064] The difference between this embodiment and embodiment 1 is as follows:

[0065] Step 3: Phosphate rock agglomeration and purification

[0066] Step 301, weighing phosphate concentrate including coarse aggregate, fine aggregate, compression molding agent, roasting aid, and water as required; the mass content of phosphorus in the phosphate concentrate is 20.49% in terms of P2O5, and the particle size distribution of the phosphate concentrate is: 15% of 1mm-2mm coarse aggregate, 85% of 0-1mm fine aggregate, wherein the mass ratio of fine aggregate smaller than 200 mesh in the fine aggregate is not less than 30%; the compression molding agent is methyl cellulose, montmorillonite, sodium hexametaphosphate according to A mixture with a mass ratio of 28:70:2, and the amount of the compression molding agent is 5% of the mass of the phosphate concentrate; the roasting aid is a mixture of sodium carbonate, quartz, kaolinite and quicklime with a mass ratio of 0.5:15:74:10.5, and the amount of the roasting aid is 2% of the mass of the phosphate concentrate; the particle size of the auxiliary material compression molding agent and the roasting aid is less than 150 mesh; the amount of water added is determined according to the moisture content of the phosphate concentrate in the compression molding in step one;

[0067] Step 302, mixing the fine aggregate weighed in step 301 with the compression molding agent, the baking aid, and the water, and then sealing and standing for 4 hours to obtain a first mixture;

[0068] Step 303, breaking up the first mixed material obtained in step 302, and passing it through a 10-mesh sieve until there is no residue left on the sieve, thereby obtaining a sieved first mixed material;

[0069] Step 304, mixing the sieved first mixture obtained in step 303 and the coarse aggregate weighed in step 1 evenly and sealing them to obtain a second mixture;

[0070] Step 305, sealing and aging the second mixed material obtained in step 304 at 15° C. for 12 hours to obtain an aged material;

[0071] Step 306, compression molding the aged material obtained in step 305 under a pressure of 20 MPa to obtain a pressed body;

[0072] Step 307, placing the pressed green body obtained in step 306 in an oven and drying at 105°C for 18 hours;

[0073] Step 308, placing the pressed green body dried in step 307 in an electric furnace for roasting to obtain purified phosphate ore; the roasting system is: first heating from room temperature to 600°C and keeping warm for 1 hour, then heating to 900°C and keeping warm for 1 hour, and then heating to 1150°C and keeping warm for 2 hours, and the heating rate is 4°C / min; the cooling system adopted after the roasting is: cooling from the roasting temperature to 1000°C and keeping warm for 1 hour, then cooling to 750°C and keeping warm for 2 hours, then cooling to 400°C and keeping warm for 1 hour, and then cooling to room temperature, and the cooling rate is 10°C / min.

[0074] After testing, the indicators of the pressed green body and purified phosphate ore obtained in this embodiment all meet the production requirements. The results are shown in Table 4 below.

[0075] Table 4 Product indicators of Example 2

[0076]

[0077] The powder rate of the purified phosphate rock after crushing in Table 4 is the mass content of the material less than 3 mm after crushing.

[0078] It can be seen from Table 4 that the pressed green body prepared in this embodiment has suitable strength and density, which meets the stacking requirements of tunnel kiln sintering. The prepared purified phosphate ore has a good sintering vitrification degree and high comprehensive economic efficiency, which can meet the requirements of subsequent processes.

[0079] Example 3

[0080] The difference between this embodiment and embodiment 1 is as follows:

[0081] Step 3: Phosphate rock agglomeration and purification

[0082] Step 301, weighing phosphate concentrate including coarse aggregate, fine aggregate, compression molding agent, roasting aid, and water as required; the mass content of phosphorus in the phosphate concentrate is 20.49% in terms of P2O5, and the particle size distribution of the phosphate concentrate is: 15% of 1mm-2mm coarse aggregate, 85% of 0-1mm fine aggregate, wherein the mass ratio of fine aggregate with a size less than 200 mesh in the fine aggregate is not less than 30%; the compression molding agent is methyl cellulose, montmorillonite, sodium hexametaphosphate, according to A mixture with a mass ratio of 28:70:2, and the amount of the compression molding agent is 5% of the mass of the phosphate concentrate; the roasting aid is a mixture of sodium carbonate, quartz, kaolinite and quicklime with a mass ratio of 0.5:15:74:10.5, and the amount of the roasting aid is 2% of the mass of the phosphate concentrate; the particle size of the auxiliary material compression molding agent and the roasting aid is less than 150 mesh; the amount of water added is determined according to the moisture content of the phosphate concentrate in the compression molding in step one;

[0083] Step 302, mixing the fine aggregate weighed in step 301 with the compression molding agent, the baking aid, and the water, and then sealing and standing for 4 hours to obtain a first mixture;

[0084] Step 303, breaking up the first mixed material obtained in step 302, and passing it through a 10-mesh sieve until there is no residue left on the sieve, thereby obtaining a sieved first mixed material;

[0085] Step 304, mixing the sieved first mixture obtained in step 303 and the coarse aggregate weighed in step 1 evenly and sealing them to obtain a second mixture;

[0086] Step 305, sealing and aging the second mixed material obtained in step 304 at 15° C. for 12 hours to obtain an aged material;

[0087] Step 306, compression molding the aged material obtained in step 305 under a pressure of 25 MPa to obtain a pressed body;

[0088] Step 307, placing the pressed green body obtained in step 306 in an oven and drying at 105°C for 18 hours;

[0089] Step 308, placing the pressed green body dried in step 307 in an electric furnace for roasting to obtain purified phosphate ore; the roasting system is: first heating from room temperature to 600°C and keeping warm for 1 hour, then heating to 900°C and keeping warm for 1 hour, and then heating to 1150°C and keeping warm for 2 hours, and the heating rate is 4°C / min; the cooling system adopted after the roasting is: cooling from the roasting temperature to 1000°C and keeping warm for 1 hour, then cooling to 750°C and keeping warm for 2 hours, then cooling to 400°C and keeping warm for 1 hour, and then cooling to room temperature, and the cooling rate is 10°C / min.

[0090] After testing, the indicators of the pressed green body and purified phosphate ore obtained in this embodiment all meet the production requirements. The results are shown in Table 5 below.

[0091] Table 5 Product indicators of Example 3

[0092]

[0093] The powder rate of the purified phosphate rock after crushing in Table 5 is the mass content of the material less than 3 mm after crushing.

[0094] It can be seen from Table 5 that the pressed green body prepared in this embodiment has suitable strength and density, which meets the stacking requirements of tunnel kiln sintering. The prepared purified phosphate ore has a good sintering vitrification degree and high comprehensive economic efficiency, which can meet the requirements of subsequent processes.

[0095] The chemical composition and mineral composition of the main material phosphate concentrate in Examples 4 and 5 of the present invention are shown in Tables 6 and 7 below, respectively.

[0096] Table 6 Chemical composition of phosphate concentrate (%)

[0097]

[0098] Table 7 Mineral composition of phosphate concentrate (%)

[0099]

[0100] Example 4

[0101] This embodiment includes the following steps:

[0102] Step 1: Determine the moisture content of compression molding

[0103] The phosphate concentrate was tested and Gp=1.3g, Gs=10.80, then the plasticity index of the phosphate concentrate, that is, the plastic limit Wp=(1.3 / 10.80)×100%=12%, and the compression molding moisture of the phosphate concentrate = plastic limit Wp-2%=12%-2%=10%; Gp is ​​the mass of water contained when the plastic state changes to a semi-solid state, and Gs is the mass of absolutely dry clay, which can be directly measured by the strip rubbing method, or obtained by the combined determination method of liquid and plastic limits;

[0104] Step 2: Determine the roasting temperature and roasting time

[0105] The roasting temperature determination process is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and sealed for 1 hour, 30g of round cake samples with a diameter of φ50mm are taken, and the round cake samples are tested after drying. The test firing temperatures are 1100℃, 1125℃, 1150℃, and 1175℃ respectively. 1200℃, heating rate 4℃ / min, holding time 30min, then the products obtained at different test firing temperatures were tested for water absorption by boiling method, the results showed that the water absorption of the product obtained at 1200℃ was 5.1%, the water absorption of the product obtained at 1175℃ was 8.7%, and the water absorption of the products obtained below 1175℃, i.e. 1100℃, 1125℃, and 1150℃ were all greater than 8%; then 2% roasting aid was added to the raw phosphate concentrate, and the above-mentioned water-added sealing aging, sample pressing, drying test firing, and water absorption rate detection process were repeated. The results showed that the water absorption of the product obtained at 1175℃ was 8.3%; 4% roasting aid was added to the raw phosphate concentrate, and the above-mentioned water-added sealing aging, sample pressing, drying test firing, and water absorption rate detection process were repeated. The results show that the water absorption rate of the product obtained at 1175℃ is 8.2%; 6% roasting aid is added to the raw phosphate concentrate, and the above-mentioned water-added sealing aging, sample pressing, drying trial firing, and water absorption rate detection process is repeated. The results show that the water absorption rate of the product obtained at 1175℃ is 8.1%; 8% roasting aid is added to the raw phosphate concentrate, and the above-mentioned water-added sealing aging, sample pressing, drying trial firing, and water absorption rate detection process is repeated. The results show that the water absorption rate of the product obtained at 1175℃ is 6.4%, and the water absorption rate of the product obtained at 1150℃ is 7.93%. The water absorption rates of the products obtained at temperatures below 1150℃, i.e., 1100℃ and 1125℃, are all greater than 8%. Therefore, the optimal firing temperature, i.e., the roasting temperature, is determined to be 1150℃, and 8% roasting aid is added at the same time;

[0106] The process of determining the roasting time is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and stirred evenly, and then it is allowed to stand for 1 hour, and then it is broken up through a 150 mesh sieve, and then sealed and aged for 2 hours. 600g~800g of the aged material is weighed and pressed into a 100mm×100mm×(30~40)mm sample, and the molding pressure is 20MPa. It is dried to constant weight for pre-burning. The pre-burning heating system is as follows: first, the temperature is increased from room temperature to 600℃ and kept for 1 hour, then the temperature is increased to 900℃ and kept for 1 hour, and then the temperature is increased to the selected optimal firing temperature, i.e., 1150℃, and kept for 1 hour, 2 hours, and 3 hours, respectively, and the heating rate is 4℃ / min. Then, the products obtained at different holding times are tested for water absorption by the boiling method. The results show that the products obtained at holding times of 1 hour and 2 hours can achieve a water absorption rate of less than 10%. Considering the energy consumption cost, the optimal holding time, i.e., the roasting time, is determined to be 1 hour.

[0107] Step 3: Phosphate rock agglomeration and purification

[0108] Step 301, weighing phosphate concentrate including coarse aggregate, fine aggregate, compression molding agent, roasting aid, and water as required; the mass content of phosphorus in the phosphate concentrate is 16.49% in terms of P2O5, and the particle size distribution of the phosphate concentrate is: 10% of 1mm-2mm coarse aggregate, 90% of 0-1mm fine aggregate, wherein the mass ratio of fine aggregate smaller than 200 mesh in the fine aggregate is not less than 30%; the compression molding agent is methyl cellulose, montmorillonite, sodium hexametaphosphate, and the like, and the weight ratio of the fine aggregate is 10%. The mixture is prepared by mixing the mixture in a mass ratio of 28:70:2, and the amount of the compression molding agent is 3.5% of the mass of the phosphate concentrate; the roasting aid is a mixture of sodium carbonate, quartz, kaolinite and quicklime in a mass ratio of 0.5:15:74:10.5, and the amount of the roasting aid is 8% of the mass of the phosphate concentrate; the particle sizes of the auxiliary material compression molding agent and the roasting aid are both less than 150 meshes; the amount of water added is determined according to the moisture content of the phosphate concentrate in the compression molding in step one;

[0109] Step 302, mixing the fine aggregate weighed in step 301 with the compression molding agent, the baking aid, and the water, and then sealing and standing for 3 hours to obtain a first mixture;

[0110] Step 303, breaking up the first mixed material obtained in step 302, and passing it through a 10-mesh sieve until there is no residue left on the sieve, thereby obtaining a sieved first mixed material;

[0111] Step 304, mixing the sieved first mixture obtained in step 303 and the coarse aggregate weighed in step 1 evenly and sealing them to obtain a second mixture;

[0112] Step 305, sealing and aging the second mixed material obtained in step 304 at 25°C for 12 hours to obtain an aged material;

[0113] Step 306, compression molding the aged material obtained in step 305 under a pressure of 23 MPa to obtain a pressed body;

[0114] Step 307, placing the pressed green body obtained in step 306 in an oven and drying at 105°C for 18 hours;

[0115] Step 308, placing the pressed green body dried in step 307 in an electric furnace for roasting to obtain purified phosphate ore; the roasting system is: first heating from room temperature to 600°C and keeping warm for 1 hour, then heating to 900°C and keeping warm for 1 hour, and then heating to 1150°C and keeping warm for 1 hour, and the heating rate is 4°C / min; the cooling system adopted after the roasting is: cooling from the roasting temperature to 1000°C and keeping warm for 1 hour, then cooling to 750°C and keeping warm for 2 hours, then cooling to 400°C and keeping warm for 1 hour, and then cooling to room temperature, and the cooling rate is 10°C / min.

[0116] After testing, the indicators of the pressed green body and purified phosphate ore obtained in this embodiment all meet the production requirements. The results are shown in Table 8 below.

[0117] Table 8 Product indicators of Example 4

[0118]

[0119] The powder rate of the purified phosphate rock after crushing in Table 8 is the mass content of materials less than 3 mm after crushing.

[0120] It can be seen from Table 8 that the pressed green body prepared in this embodiment has suitable strength and density, which meets the stacking requirements of tunnel kiln sintering. The prepared purified phosphate ore has a good sintering vitrification degree and high comprehensive economic efficiency, which can meet the requirements of subsequent processes.

[0121] Example 5

[0122] The difference between this embodiment and embodiment 1 is as follows:

[0123] Step 3: Phosphate rock agglomeration and purification

[0124] Step 301, weighing phosphate concentrate including coarse aggregate, fine aggregate, compression molding agent, roasting aid, and water as required; the mass content of phosphorus in the phosphate concentrate is 16.49% in terms of P2O5, and the particle size distribution of the phosphate concentrate is: 15% of 1mm~2mm coarse aggregate, 85% of 0~1mm fine aggregate, wherein the mass ratio of fine aggregate smaller than 200 mesh in the fine aggregate is not less than 30%; the compression molding agent is methyl cellulose, montmorillonite, sodium hexametaphosphate according to A mixture with a mass ratio of 28:70:2, and the amount of the compression molding agent is 5% of the mass of the phosphate concentrate; the roasting aid is a mixture of sodium carbonate, quartz, kaolinite and quicklime with a mass ratio of 0.5:15:74:10.5, and the amount of the roasting aid is 8% of the mass of the phosphate concentrate; the particle size of the auxiliary material compression molding agent and the roasting aid is less than 150 mesh; the amount of water added is determined according to the moisture content of the phosphate concentrate in the compression molding in step one;

[0125] Step 302, mixing the fine aggregate weighed in step 301 with the compression molding agent, the baking aid, and the water, and then sealing and standing for 3 hours to obtain a first mixture;

[0126] Step 303, breaking up the first mixed material obtained in step 302, and passing it through a 10-mesh sieve until there is no residue left on the sieve, thereby obtaining a sieved first mixed material;

[0127] Step 304, mixing the sieved first mixture obtained in step 303 and the coarse aggregate weighed in step 1 evenly and sealing them to obtain a second mixture;

[0128] Step 305, sealing and aging the second mixed material obtained in step 304 at 25°C for 12 hours to obtain an aged material;

[0129] Step 306, compression molding the aged material obtained in step 305 under a pressure of 25 MPa to obtain a pressed body;

[0130] Step 307, placing the pressed green body obtained in step 306 in an oven and drying at 105°C for 18 hours;

[0131] Step 308, placing the pressed green body dried in step 307 in an electric furnace for roasting to obtain purified phosphate ore; the roasting system is: first heating from room temperature to 600°C and keeping warm for 1 hour, then heating to 900°C and keeping warm for 1 hour, and then heating to 1150°C and keeping warm for 1 hour, and the heating rate is 4°C / min; the cooling system adopted after the roasting is: cooling from the roasting temperature to 1000°C and keeping warm for 1 hour, then cooling to 750°C and keeping warm for 2 hours, then cooling to 400°C and keeping warm for 1 hour, and then cooling to room temperature, and the cooling rate is 10°C / min.

[0132] After testing, the indicators of the pressed green body and purified phosphate ore obtained in this embodiment all meet the production requirements. The results are shown in Table 9 below.

[0133] Table 9 Product indicators of Example 5

[0134]

[0135] The powder rate of the purified phosphate rock after crushing in Table 9 is the mass content of the material less than 3 mm after crushing.

[0136] It can be seen from Table 9 that the pressed green body prepared in this embodiment has suitable strength and density, which meets the stacking requirements of tunnel kiln sintering. The prepared purified phosphate ore has a good sintering vitrification degree and high comprehensive economic efficiency, which can meet the requirements of subsequent processes.

[0137] Example 6

[0138] The chemical composition and mineral composition of the main material phosphate concentrate in this embodiment are shown in Tables 10 and 11 respectively.

[0139] Table 10 Chemical composition of phosphate concentrate (%)

[0140]

[0141] Table 11 Mineral composition of phosphate concentrate (%)

[0142]

[0143] This embodiment includes the following steps:

[0144] Step 1: Determine the moisture content of compression molding

[0145] The phosphate concentrate was tested and Gp=0.29g, Gs=6.7, so the plasticity index of the phosphate concentrate, that is, the plastic limit Wp=(0.29 / 6.7)×100%=4.3%. Since the plastic limit Wp of the phosphate concentrate is less than 5%, it is considered that the material is not suitable for the method of the present invention.

[0146] Example 7

[0147] The chemical composition and mineral composition of the main material phosphate concentrate in this embodiment are shown in Tables 12 and 13 respectively.

[0148] Table 12 Chemical composition of phosphate concentrate (%)

[0149]

[0150] Table 13 Mineral composition of phosphate concentrate (%)

[0151]

[0152] This embodiment includes the following steps:

[0153] Step 1: Determine the moisture content of compression molding

[0154] The phosphate concentrate was tested and Gp=1.4g, Gs=10.90, then the plasticity index of the phosphate concentrate, that is, the plastic limit Wp=(1.4 / 10.90)×100%=12.8%, the compression molding moisture of the phosphate concentrate = plastic limit Wp-2%=12.8%-2%=10.8%; Gp is ​​the mass of water contained when the plastic state changes to a semi-solid state, and Gs is the mass of absolutely dry clay, which can be directly measured by the strip rubbing method, or obtained by the combined determination method of liquid and plastic limits;

[0155] Step 2: Determine the roasting temperature and roasting time

[0156] The roasting temperature determination process is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and sealed for aging for 1h, 30g of round cake samples with a diameter of φ50mm are taken, and the round cake samples are tested after drying. The test firing temperatures are 1100℃, 1125℃, 1150℃, 1175℃, and 1200℃, respectively. The heating rate is 4℃ / min, and the holding time is 30min. Then, the products obtained at different test firing temperatures are tested for water absorption by the boiling method. The results show that the water absorption of the product obtained at 1200℃ is 5.7%, the water absorption of the product obtained at 1175℃ is 11.9%, and the water absorption of the products obtained below 1175℃, i.e., 1100℃, 1125℃, and 1150℃ is greater than 8%; then 2% roasting aid is added to the raw phosphate concentrate to repeat the above-mentioned water-added sealing aging, sample pressing, drying test firing, and water absorption detection process. The results show that: The water absorption rate of the product obtained at 75°C is 10.3%; 4% of roasting aid is added to the raw phosphate concentrate, and the above-mentioned water-adding sealing aging, sample pressing, drying trial firing, and water absorption rate detection process is repeated. The results show that the water absorption rate of the product obtained at 1175°C is 9.7%; 6% of roasting aid is added to the raw phosphate concentrate, and the above-mentioned water-adding sealing aging, sample pressing, drying trial firing, and water absorption rate detection process is repeated. The results show that the water absorption rate of the product obtained at 1175°C is 9.2%; 8% of roasting aid is added to the raw phosphate concentrate, and the above-mentioned water-adding sealing aging, sample pressing, drying trial firing, and water absorption rate detection process is repeated. The results show that the water absorption rate of the product obtained at 1175°C is 8.9%, and the water absorption rate of the product obtained at 1150°C is 9.75%. The water absorption rates of the products obtained at temperatures below 1150°C, i.e., 1100°C and 1125°C, are all greater than 8%. Therefore, it is considered that the raw phosphate concentrate is not suitable for the method of the present invention.

[0157] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for agglomerating and purifying phosphate rock by compression molding, characterized in that: The method uses phosphate concentrate as a main material, and compression molding agent and roasting aid as auxiliary materials. The phosphate concentrate including coarse aggregate and fine aggregate, the compression molding agent, the roasting aid and water are weighed as needed, and the materials are mixed, left to stand, dispersed, aged, compression molded, dried and roasted in sequence to prepare a block-shaped purified phosphate concentrate. The phosphorus mass content in the phosphate concentrate is 15% to 25% in terms of P2O5, and the particle gradation of the phosphate concentrate is: 10% to 15% of 1mm to 2mm coarse aggregate, 85% to 90% of 0 to 1mm fine aggregate, wherein the fine aggregate is 10% to 15% of 0 to 1mm coarse aggregate, 85% to 90% of 0 to 1mm fine aggregate, and the fine aggregate is 10% to 15% of 0 to 1mm coarse aggregate, 85% to 90% of 0 to 1mm coarse aggregate, and 85% to 90% of 0 to 1mm coarse aggregate. The mass ratio of fine aggregates less than 200 mesh is not less than 30%; the compression molding agent is a mixture of methyl cellulose, montmorillonite and sodium hexametaphosphate in a mass ratio of 28:70:2, and the blending amount of the compression molding agent is 3% to 5% of the mass of the phosphate concentrate; the roasting aid is a mixture of sodium carbonate, quartz, kaolinite and quicklime in a mass ratio of 0.5:15:74:10.5, and the blending amount of the roasting aid is 2% to 8% of the mass of the phosphate concentrate; the particle size of the auxiliary material compression molding agent and the roasting aid is less than 150 mesh; The compression molding is a method of using pressure to press the material placed in the mold to a compact structure to form a green body with a certain shape and strength, wherein the moisture content of the material placed in the mold is the compression molding moisture, which has the following meanings: Compression molding moisture = plastic limit Wp-2% =(Gp / Gs)×100%-2% Gp is ​​the mass of water contained when the plastic state changes into a semi-solid state; Gs is the mass of absolutely dry clay, which is directly measured by the strip method, or obtained by the combined measurement of liquid and plastic limits; when the moisture content of compression molding is less than 5%, the material is considered not suitable for this method.

2. The method for agglomeration and purification of phosphate rock by compression molding according to claim 1, characterized in that: The method comprises the following steps: Step 1, weighing phosphate concentrate including coarse aggregate, fine aggregate, compression molding agent, roasting aid, and water as required; Step 2: Mix the fine aggregate weighed in step 1 with the compression molding agent, the baking aid, and the water, and then seal and let stand for 2 hours to 4 hours to obtain a first mixture; Step 3, breaking up the first mixed material obtained in step 2, and passing it through a 10-mesh sieve until there is no residue left, thereby obtaining a sieved first mixed material; Step 4: Evenly mix the sieved first mixture obtained in step 3 and the coarse aggregate weighed in step 1 and seal the mixture to obtain a second mixture; Step 5: sealing and aging the second mixed material obtained in step 4 at 15° C. to 25° C. for 8 h to 12 h to obtain an aged material; Step 6: Compression-molding the aged material obtained in step 5 at a pressure of 20 MPa to 25 MPa to obtain a pressed body; Step 7: Place the pressed green body obtained in step 6 in an oven and dry at 105°C for 12h~18h; Step 8: Place the pressed green body dried in step 7 in an electric furnace for roasting to obtain purified phosphate ore.

3. The method for agglomeration and purification of phosphate rock by compression molding according to claim 2, characterized in that: The roasting temperature determination process described in step eight is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and sealed for 1h, 30g of round cake samples with a diameter of φ50mm are taken and pressed, and the round cake samples are trial-fired after drying. The trial firing temperatures are 1100°C, 1125°C, 1150°C, 1175°C and 1200°C, respectively, with a heating rate of 4°C / min and a holding time of 30min. Then, the products obtained at different trial firing temperatures are tested for water absorption by the boiling method. When the water absorption of the product is 5% to 8%, the corresponding minimum firing temperature is considered to be the optimal firing temperature, i.e., the roasting temperature. When the minimum firing temperature is higher than 1175°C, 2% roasting aid is added to the raw phosphate concentrate in batches, and water is added to seal and age, sample is pressed, dried and fired, and the water absorption rate is tested to reduce the minimum firing temperature. When the amount of roasting aid added is greater than 8%, the minimum firing temperature cannot be reduced, and it is considered that the material is not suitable for this method. The roasting time determination process is as follows: the phosphate concentrate is dried and ground to 200 mesh, 3% water is added and stirred evenly, and then the mixture is allowed to stand for 1 hour, and then the mixture is broken up through a 150-mesh sieve, and then sealed and aged for 2 hours. 600g~800g of the aged material is weighed and pressed into a 100mm×100mm×30~40mm sample, and the molding pressure is 20MPa. The sample is dried to constant weight for pre-burning, and the pre-burning heating system is as follows: first, the temperature is increased from room temperature to 600°C and kept for 1 hour, then the temperature is increased to 900°C and kept for 1 hour, and then the temperature is increased to the selected optimal firing temperature for keeping warm. The keeping warm times are 1 hour, 2 hours, and 3 hours, respectively, and the heating rate is 4°C / min. Then, the products obtained at different keeping warm times are tested for water absorption by the boiling method. When the water absorption of the product is less than 10%, the corresponding minimum keeping warm time is considered to be the optimal keeping warm time.

4. The method for agglomeration and purification of phosphate rock by compression molding according to claim 2, characterized in that: The cooling system adopted after roasting in step eight is: cooling from the roasting temperature to 1000°C and keeping it for 1 hour, then cooling to 750°C and keeping it for 2 hours, then cooling to 400°C and keeping it for 1 hour, and then cooling to room temperature, and the cooling rate is 10°C / min.

Citation Information

Patent Citations

  • Slagging fluxing agent for production of electric furnace-process yellow phosphorus

    CN106495111A

  • Preparation method of raw phosphorite for yellow phosphorus production and raw phosphorite

    CN118387845A

Cited By

  • A method of purifying by continuous mixing and compression molding by internal combustion

    CN122831299A